Classrooms to Networks: Applying Connectivism Principles in Pedagogy ``` - Desak Putu Jeny (Journal of Pedagogi, 2024)
The integration of digital technologies has led to a significant transformation in educational practices, shifting from traditional classroom models to more dynamic, networked learning environments. This paper explores the concept of connectivism, a learning theory developed by Siemens and Downes, which emphasizes the importance of networks, connectivity, and collaboration in acquiring knowledge. Unlike traditional pedagogies that focus on content delivery, connectivism promotes the creation and navigation of networks to facilitate continuous learning. Key principles of connectivism include the diversity of opinions, the distribution of knowledge across networks, and the critical role of digital tools in learning processes. The paper discusses the practical applications of connectivism approaches in contemporary pedagogy, focusing on how educators can transform traditional classrooms into engaging, networked learning spaces. Despite its theoretical strengths, the implementation of connectivism faces challenges, including technological access, information management, and the need for pedagogical adaptation. Through this exploration, the paper aims to provide insights into how connectivism can enhance educational practices and prepare students for the complexities of a rapidly evolving, networked society.